1988
DOI: 10.1177/096032718800700510
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology

Abstract: 1 Ecotoxicology is concerned ultimately with the effects of pollutants on populations not individuals. Sub-lethal effects, and changes to the environment, can have a greater impact on population size than does acute toxicity. 2 Effective concern about effects of pollutants on wildlife developed after the Second World War with the advent of synthetic pesticides, and the difficulties encountered then in the evaluation of the effects of insecticides are still with us. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The EC20 and EC50 indexes were determined by linear regression of the biological factor as a function of the logarithmic effluent concentration (Moriarty 1988). The acute toxicity index was calculated using the mean effective concentration (ATU = 100/EC50) and classified according to table 1.…”
Section: Ecotoxicological Analyzesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EC20 and EC50 indexes were determined by linear regression of the biological factor as a function of the logarithmic effluent concentration (Moriarty 1988). The acute toxicity index was calculated using the mean effective concentration (ATU = 100/EC50) and classified according to table 1.…”
Section: Ecotoxicological Analyzesmentioning
confidence: 99%
“…The ecotoxicology assesses the impact of pollutants in the scale of populations, communities and ecosystems, through the use of testing organisms (Hoffman et al 2002). Ecotoxicological parameters are used to forecast the transformation processes of pollutants in the environment at different trophic levels (Moriarty 1988;Costa et al 2008;Gavrilescu 2010). In this context, the objective of this study was to collect a sample of textile effluent from a plant located in the southeast Equation 1…”
Section: Introductionmentioning
confidence: 99%
“…Decreases recorded between 1990 and 2014, which were indicated in the previous review of the implementation of environmental policy, continued to be observed between 2014 and 2016: emissions of sulphur oxides (SOx) decreased by 18.63% and ammonia (NH3) by 1.02%. Between 2014 and 2016, volatile organic compound (VOC) emissions increased by 3.04%, fine PM 2.5 by 3.83% and nitrogen oxides (NOx) by 0.05% (Akimoto, 2003;Guerreiro et al, 2014;Moriarty, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The term ecotoxicology has been applied to the field of study focused on the effects of toxic chemicals on biological organisms, at the population, community, ecosystem level (Moriarty, 1988); Ecotoxicoparasitology , however, relates to the interface of three disciplines, and is concerned with complex systems including parasites, their hosts, and the toxicants to which they are exposed.…”
Section: Introductionmentioning
confidence: 99%